The Knowledge Management of Employees of Lao Telecommunication Public Company in four provinces in the north of Lao PDR: https://doi.org/10.69692/SUJMRD100438 - LUENAMMACHAK, INTHACHONE; YANGSANSAY, Chahue; NOUANTHASING, Kommaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of the research were: 1) To study the level of knowledge management of employees of the Lao Telecommunication Public Company, 2) To study the level of factors influencing knowledge management of Employees of Lao Telecommunication Public Company and 3) To study the factors affecting the knowledge management of employees of the Lao Telecommunication Public Company in four provinces in the northern part of Lao PDR. The simple was 128 staff members of Lao telecommunication public company in four northern provinces of Lao PDR. A questionnaire was used as a research instrument for data collection. Data collected were then analyzed using descriptive analysis to determine frequency, percentage, mean and standard deviation and multiple regression analysis by stepwise method. The results of the study found that: 1) The level of knowledge management of employees of Lao telecommunication public company was at high level (m=4.16, s=0.57) and consisted of seven aspects such as: knowledge identification, knowledge acquisition, knowledge dissemination, knowledge organization, knowledge creation, knowledge application and learning respectively. 2) The level of factors influencing knowledge management of employees of Lao telecommunication public company was at high level (m=4.14, s=0.50) and consisted of seven aspects such as: vision factors, leadership factors, technology factors, structure factors, measurement factors, culture organization factors, strategy factors respectively. 3) The factors affecting the knowledge management of employees of the Lao Telecommunication Public Company in four provinces in the northern part of Lao PDR, which consisted of two factors such as: structure factors, leadership factors and measurement factors at a significant level of 0.05. The equation can predict the knowledge management of employees of the Lao telecommunication public company in four northern provinces of Lao PDR as a whole up to 80.50%.